The Effect of Cake Application on Students’ Speaking Skill at the Eleventh Grade of Senior High School 14 Pekanbaru - Eldania, Inda; Yusrida, Yusrida (Journal of English and Arabic Language Teaching, 2024)
Cake application is an English learning application that aims to improve student learning activities in English. This application provides speaking, writing, listening, and reading features. There are several features in this application such as watching short movie and practicing speaking by using dialogue. The aimed of this research was to find out whether there is a significant difference of students’ speaking skill between before and after using Cake application at the Eleventh Grade of Senior High School 14 Pekanbaru. The researcher formulated the problems into three research questions that would be answering by using quantitative research. This research was a pre-experimental research. The total population was 422 students. The classes chosen as the sample was XI IPA 7 by using a convenience sampling technique which the total of sample were 36 students’. In collecting the data, the researcher used speaking test to determine students’ speaking skill. In analyzing the data, the researcher used Wilcoxon signed Ranks Test formula calculated by SPSS 23 version. Based on analysis of the t-test formula, the sig. value is 0.000. It could be stated that 0.000 had less value than 0.05, then Ha is accepted and Ho is rejected. So it can be concluded that there was a significant difference of students’ speaking skill between before and after using Cake application at the Eleventh Grade of Senior High School 14 Pekanbaru.